El liderazgo en el Mercosur frente al dilema etanol vs. petróleo - Marina Valle, Valeria (Revista Mexicana de Política Exterior, 2022)
Today’s global scenario poses new challenges to political and economic integration, an issue that is broached by Valeria Marina Valle in her paper on the Mercosur economic community. As a re gional integration process based on inter-governmental relations, Mercosur leaders have acquired important standing, often overshadowing the fledgling institutions they represent. According to the author, the structure of Mercosur has great bearing on political alliances, with Brazil stepping up as the community’s natural leader. However, since Venezuela joined its ranks, Hugo Chávez has also emerged as a leader, resulting in debate on two opposing energy bills: Venezuelan oil versus Brazilian ethanol, a dilemma that the author goes on to analyze in depth. Regional integration or fragmentation, concludes Marina Valle, could hinge on the political alliances or antagonisms formed within Mercosur.